Structured Chemical Safety Multimedia Courseware For Secondary Schools Chemistry Teachers - Narayanasamy, Prabadevi (2014)
Interactive multimedia courseware is one of the modalities that being implemented in self-teaching with attentive features which make adult learning interesting and effectives. The study aims is to establish interactive multimedia courseware that empowers national secondary schools chemistry teachers with adequate knowledge for safe conduct of chemistry practical’s by students. In achieving the aim, three specifics objectives were identified, i.e. (1) to profile chemistry teacher’s background, (2) to gauge chemistry teachers’ knowledge of chemical safety and knowledge of facility for handling hazardous chemical and (3) to develop an interactive multimedia courseware for chemical safety education for chemistry teachers (MyChemiSOS) up to alpha version.